Acquire skills, Regent tells university students - Siti Nur Azwin, Zulkapri (The New Straits Times Press (M) Bhd, 2020)
KUANTAN: Pahang Regent Tengku Hassanal Ibrahim Alam Shah ibni Al-Sultan Abdullah Ri’ayatuddin Al-Mustafa Billah Shah advised university students to avoid the 3K Syndrome of Kuliah - Kafeteria - Katil (Lecture - Cafeteria - Bed).